The Relationship Between Playing Games Contains an Element of Violence with Aggressive Behavior of Students - Winda Aprilia Gusti; Mudjiran Mudjiran (Universitas Negeri Padang, 2019)
Adolescents are developing individuals who are looking for their identity. In the period of seeking identity, they will find various problems, which they can solve their own problems, not infrequently they cannot overcome their own problems so they are burdened and hamper their developmental tasks. One of the changes related to psychology in adolescents is that it is easy to react even aggressively to the interference or external stimulation that affects it. That is why there is an easy fight. Like to look for attention and act without thinking first. Aggressive behavior is one form of behavior whose purpose and intention is to intentionally harm others. One of the factors that causes adolescents to behave aggressively is the violence that exists in the media such as playing games that contain elements of violence. This study aims to determine the relationship between playing games that contain elements of violence and aggressive behavior of students in the Middle School of Padang State University Laboratory Development. The results of this study revealed that: (1) playing games containing elements of violence in terms of aspects of the type of game and the frequency of playing games are in the quite high category. This means that students are quite high in playing games that contain elements of violence. (2) students' aggressive behavior in terms of aspects of ggressiveness / physical aggression (verbal aggression), verbal aggression, anger, and hostility are in the category of very high. This means that some students behave aggressively towards others. (3) there is a positive relationship between playing games containing violent elements with aggressive behavior of students in SMP Pembangunan Laboratorium UNP a correlation coefficient of 0.351, which means that the higher the level of playing games that contain elements of violence the higher the aggressive behavior of junior high school students, and vice versa the lower the level of playing games that contain elements of violence, the lower the aggressive behavior of middle school students